Kolaborasi dan Produktivitas Pengarang Artikel Jurnal Khizanah Al-Hikmah: Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan Tahun 2013 – 2020 - Hayani, Liswa; Sudiar, Nining; Amelia, Vita (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2022)
The purpose of this research is to find out how the level of collaboration and productivity of the author in the Khizanah Al-Hikmah Journal article: Journal of Library, Information and Archive Science 2013-2020 UIN Alauddin Makassar. The population and sample in this study were all articles published in the journal Khizanah Al-Hikmah Journal: Journal of Library, Information and Archive Science in the last eight years 2013-2020. The method used in this research is descriptive quantitative research with a quantitative approach. The results of this study indicate that the results show that the number of articles from 2013-2020 was 142 articles. The average collaboration level is 0.40. The number of authors was 245 people. The most productive authors are Taufik Mathar and Tupan with 7 articles. We found that the top 5 agencies contributing to articles were UIN Alauddin Makassar (25.31%), Padjajaran University (13.47%), PDII LIPI (11.84%), Sunan Kalijaga State Islamic University (6.53%), Brawijaya University (4.9%). Affiliates with public status are 95.51% and private 4.49%. It can be concluded that most of the articles were written collaboratively, namely 56 articles, most of the writers' affiliations came from institutions of higher education libraries (81.63%).